Panduratin a inhibits the growth of A549 Cells through induction of apoptosis and inhibition of NF-KappaB translocation - Cheah, S.C.; Appleton, D.R.; Lee, S.T.; Lam, M.L.; Hadi, A.H.A.; Mustafa, Mohd Rais (Springer Verlag (Germany), 2011)
In the present study we investigated the effects of panduratin A, isolated from Boesenbergia rotunda, on proliferation and apoptosis in A549 human non-small cell lung cancer cells. Cell proliferation and induction of apoptosis was determined by the real-time cellular analyzer (RTCA), MTT assay and High Content Screening (HCS). The RTCA assay indicated that panduratin A exhibited cytotoxicity, with an IC50 value of 4.4 µg/mL 10.8 µM). Panduratin A arrested cancer cells labeled with bromodeoxyuridine (BrdU) and phospho-Histone H3 in the mitotic phase. The cytotoxic effects of panduratin A were found to be accompanied by a dose-dependent induction of apoptosis, as assessed by DNA condensation, nuclear morphology and intensity, cell permeability, mitochondrial mass/potential, F-actin and cytochrome c. In addition, treatment with an apoptosis-inducing concentration of panduratin A resulted in significant inhibition of Nuclear Factor-kappa Beta (NF-κB) translocation from cytoplasm to nuclei activated by tumor necrosis factoralpha (TNF-α), as illustrated by the HCS assay. Our study provides evidence for cell growth inhibition and induction of apoptosis by panduratin A in the A549 cell line,suggesting its therapeutic potential as an NF-κB inhibitor.